VÍCTOR PÉREZ ESCOLANO, CARLOS PLAZA (coords.) - Manfredo Tafuri: desde España - Sanz Esquide, José Ángel (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
Víctor Pérez Escolano, Carlos Plaza (coords.)Manfredo Tafuri: desde EspañaGranada: Patronato de la Alhambra y Generalife, 2020. 447 pp. Digital Open Access. Language: Spanish https://es.calameo.com/books/004924697ac235a2bd23e